Ibrutinib significantly inhibited Bruton's tyrosine kinase (BTK) phosphorylation, in-vitro proliferation and enhanced overall survival in a preclinical Burkitt lymphoma (BL) model. (2nd January 2019) - Chu, Yaya; Lee, Sanghoon; Shah, Tishi; Yin, Changhong; Barth, Matthew; Miles, Rodney R.; Ayello, Janet; Morris, Erin; Harrison, Lauren; Van de Ven, Carmella; Galardy, Paul; Goldman, Stanton C.; et al.
ABSTRACT: Pediatric and adult patients with recurrent/refractory Burkitt lymphoma (BL) continue to have poor outcomes, emphasizing the need for newer therapeutic agents. Bruton's tyrosine kinase (BTK) is activated following B-cell receptor stimulation and in part regulates normal B-cell development. Ibrutinib, a selective and irreversible BTK inhibitor, has been efficacious in chronic lymphocytic leukemia (CLL), mantle cell lymphoma (MCL), Waldenström's macroglobulinemia, and marginal zone lymphoma. In this study, we investigated the efficacy of ibrutinib alone and in selective adjuvant combinations against BL in-vitro and in a human BL xenografted immune-deficient NOD.Cg-Prkdc scid Il2rg tm1Wjl /SzJ (NSG) mouse model. Our data demonstrated that phospho-BTK level was significantly reduced in BL cells treated with ibrutinib (p < 0.001). Moreover, we observed a significant decrease in cell proliferation as well as significant decrease in IC50 of ibrutinib in combination with dexamethasone, rituximab, obinutuzumab, carfilzomib, and doxorubicin (p < 0.001). In-vivo studies demonstrated ibrutinib treated mice had a significantly prolonged survival with median survival of mice following ibrutinib treatment (32 days) (24 days) (p < 0.02). In conclusion, our findings demonstrate the significant in-vitro and preclinical in-vivo effects of ibrutinib in BL. Based on our preclinical results in this investigation, there is an on-going clinical trial comparing overall survival in children and adolescents with relapsed/refractory BL treated with chemoimmunotherapy with or without ibrutinib (NCT02703272).